Cutaneous angiosarcoma of head and neck - Rita Vora; Gopikrishnan Anjaneyan; Rajat Gupta (Wolters Kluwer Medknow Publications, 2014)
Cutaneous angiosarcoma is a rare aggressive tumor of capillary and lymphatic endothelial cell origin. Cutaneous angiosarcoma of the head and neck regions seems to be a distinctive neoplasm with characteristic clinicopathologic features that differ from angiosarcoma in other anatomic locations. Angiosarcoma, regardless of their setting, has a bad prognosis. We presented here a case of 80 years old male, with multiple nontender grouped purple to red hemorrhagic vesicular and bullous lesions over left lower cheek and upper neck area, with bilateral cervical lymph nodes since 1 month. Computed tomography thorax showed nodular opacities in the right upper and midzones. Excisional biopsy showed characterstic "dissection of collagen" with mild nuclear atypia. Immunohistochemistry showed tumor cell positive for CD-31 and Fli-1. Patient died within 1 month of presentation.